Implications of the COVID-19 infodemic for scientific communication and diffusion: An integrative review - Fagá, Mariana de Almeida Prado; Cyrino, Antonio Pithon; Teixeira, Ricardo Rodrigues (Revista Española de Comunicación en Salud, 2025)
Introduction: The COVID-19 infodemic complicated public adherence to public health measures during the pandemic and required strategies to improve communication and scientific dissemination. Objective: To review the literature on the implications of the infodemic for communication and scientific dissemination. Methodology: An integrative review was conducted based on a systematic search in the MEDLINE/PubMed, Scielo, Scopus, and Web of Science (WoS) databases between March and April 2024. A total of 62 articles were selected for analysis. Results: The articles were grouped into three main themes: (1) The impact of the COVID-19 pandemic on scientific communication; (2) Infodemic control; and (3) Communication and scientific dissemination practices. Discussion: The widespread use of social media intensified communication and scientific dissemination but also amplified the spread of misinformation, requiring strategies for information control and greater collaboration among scientists, media, and government organizations. Scientific literacy and community engagement with science were widely recommended. Conclusion: It is essential to preserve the integrity of science and promote open dialogue between scientists and the public to improve trust and understanding of science.